Intrathecal rituximab for the treatment of Epstein–Barr virus-associated encephalitis - Chapuis, Aude G.; Orozco, Johnnie J.; Milano, Filippo (Frontiers in Immunology, 2025)
Epstein–Barr virus (EBV)-associated encephalitis is seen in patients who have undergone allogeneic hematopoietic stem cell transplant and can be associated with significant morbidity and mortality. The mainstay of treatment has been antiviral therapy with nucleoside analogues and reduction of immunosuppression. Here, we describe an adult patient diagnosed with refractory EBV-associated encephalitis within 30 days post-allogeneic transplant successfully treated with intrathecal rituximab, which, to our knowledge, is the first case treated in this manner.